1980
DOI: 10.1002/pssa.2210600227
|View full text |Cite
|
Sign up to set email alerts
|

Athermal annealing of structure damage in GaAs

Abstract: The results are analysed of athermal annealing of structure defects, which are the nonradiative recombination centres in irradiated p‐GaAs. Annealing processes are studied by the recovery of electroluminescence quantum yield upon nonequilibrium charge‐carrier injection in the range of 77 to 300 K. The experimental data analysis makes it possible to suggest that upon charge‐carrier injection activation of migration takes place of B‐type defects with the level Ec – 0.03 eV, which are the sticking centres for ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…It is observed that the defect removal rate 𝜆 follows an exponential law, which is similar to the following 056102-2 form of the Arrhenius law [10] 𝜆 = 𝜆 0 exp(−𝐸 in,ex /𝑘 B 𝑇 ),…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…It is observed that the defect removal rate 𝜆 follows an exponential law, which is similar to the following 056102-2 form of the Arrhenius law [10] 𝜆 = 𝜆 0 exp(−𝐸 in,ex /𝑘 B 𝑇 ),…”
mentioning
confidence: 61%
“…The fraction of unannealed defects versus the injection-enhanced annealing time follows a first-order kinetic. [10] Therefore, the radiation-induced defects are annihilated in accordance with…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Athermal effects can cause defect recovery, strain relaxation, gas and defect diffusion, phase transformations, and gas resolution from bubbles. Such transient irradiation-induced processes are experimentally well documented in the literature for ceramics (Lang 1976, Lomako 1980, Lang 1982, Assmann 1978, Matzke 1983, Matzke 2000, Zinkle 2002) under neutron, fission, ion, electron and laser irradiations. These processes are often referred to as athermal because they are temperature independent or weakly dependent on temperature and cannot be described as thermally activated (activation energies below 0.2 eV).…”
Section: Differences In Irradiation Parametersions Vs Neutronsmentioning
confidence: 82%